Pengaruh Pemberian Pupuk Hayati dan Pupuk N, P, K Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) - Muhammad Ma'ruf; Nelvia Nelvia; Fetmi Silvina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The research aims to study the effect of the application ultra gen biofertilizer and N, P, K fertilizer on the growth and production of onion (Allium ascalonicum L.). The research was conducted at Agricultural Faculty Experimental Unit, University of Riau, Pekanbaru. The research in form factorial experimentally 5x3 arranged in a completely randomized design. The first factor was ultra gen biofertilizer consists of 5 levels (without, 50, 100, 150 and 200 l.ha-1). The second factor was a N, P, K fertilizer consists of 3 levels (without, 100 kg N + 45 kg P2O5 + 37,5 kg K2O and 200 kg N + 90 kg P2O5 + 75 kg K2O.ha-1), each combination was repeated 3 times. The parameters observed were number of bulb per clump, circumference of bulb, weight of bulb fresh per clump, weight of bulb fresh per plot and weight of bulb consumption per plot. The application of ultra gen biofertilizer doses of 100 l.ha-1and N, P, K fertilizer 100 kg N + 45 kg P2O5 + 37,5 kg K2O.ha-1 increased weight of bulb fresh per clump, weight of bulb fresh per plot and weight of bulb consumption per plot significantly compared to another combination, but not significantly on number of bulb per clump and circumference of bulb.